A novel hollow cylinder apparatus to investigate shearing characteristic of asphalt - Tekieli, Katarzyna (2019)
The design and testing of asphalt to minimise wheel track rutting in highways and the prediction of its development with time remain areas requiring improved technology. Simple tests such as wheel tracking and repeated load compression are, at best, approximate and rely on empirical calibration against field performance. In the US, the Superpave Shear Test (SST) was developed during the Strategic Highway Research Program (SHRP) but, while this has proved useful, question marks remain about its reliability for fundamental research.